6x-9y=18

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 6x from both sides of the equation.

-9y=18-6x

Divide each term by -9 and simplify.

Divide each term in -9y=18-6x by -9.

-9y-9=18-9+-6x-9

Cancel the common factor of -9.

Cancel the common factor.

-9y-9=18-9+-6x-9

Divide y by 1.

y=18-9+-6x-9

y=18-9+-6x-9

Simplify 18-9+-6x-9.

Simplify each term.

Divide 18 by -9.

y=-2+-6x-9

Cancel the common factor of -6 and -9.

Factor -3 out of -6x.

y=-2+-3(2x)-9

Cancel the common factors.

Factor -3 out of -9.

y=-2+-3(2x)-3(3)

Cancel the common factor.

y=-2+-3(2x)-3⋅3

Rewrite the expression.

y=-2+2×3

y=-2+2×3

y=-2+2×3

y=-2+2×3

Reorder -2 and 2×3.

y=2×3-2

y=2×3-2

y=2×3-2

Rewrite in slope-intercept form.

y=23x-2

y=23x-2

Using the slope-intercept form, the y-intercept is -2.

b=-2

Find the Y-Intercept 6x-9y=18